Analys Of Raw Materials Cost And Labor Productivitty On Production Result - Alief Anugrah Munggaran; Suci Putri Lestari; Arga Sutrisna (Journal of Indonesian Management, 2022)
The purpose of this study is to identify and analyze of raw materials and labor productivity on production result of Alief Collection. The method of research used was case studies. The analysis tool using multiple llinear regression. The data used is primary and secondary data. Research has found that cost of raw materials and labor productivity simultaneously are significant impact on production result of Alief Collection. The cost of raw materials is partially significant to production redsult. The labor productivity is partially significant to production result. There for Ms. Ucu Yuliantin as the owner of Alief Collection must pay attention to any expenditure on raw material cost that will effect the production result and pay attention to labor productivity to increase the production result of Alief Collection Tasikmalaya City.